Environmental Health Risks and E. coli Concentration in Drinking Water from Refill Stations in Palembang (Cross-Sectional Study) - Mery Astri Yanni (BKM Public Health and Community Medicine, 2024)
Purpose: To determine the relationship between environmental health risks (EHR) (including outdoor area, building design and facilities, handlers/operators, equipment, and raw water) and the concentration of E. coli in drinking water produced by drinking water refill stations (DAMIU) in Palembang. Methods: This cross-sectional study utilized primary data on the EHR of DAMIU and water sampling from 106 registered refill stations in Palembang. Samples were randomly and proportionally selected from 18 sub-districts. The EHR checklist combined the Ministry of Health's Food Hygiene and Sanitation Guidelines and WHO's Sanitation Inspection Kiosk. E. coli concentration was determined using the membrane filter method. Variables were analyzed using univariate and bivariate analyses. Results: The average E. coli concentration (SD) in water before and after treatment was 82 CFU/100 mL (121 CFU/100 mL) and 18 CFU/100 mL (45 CFU/100 mL), respectively. There was a significant difference in the average E. coli levels between raw and produced drinking water (Z = -6.260; p < 0.001). The average (SD) EHR scores were: outdoor area 68.39% (18.38%), building design and facilities 71.11% (12.80%), handlers/operators 40.57% (10.46%), equipment 67.14% (10.91%), and raw water 18.42% (45.15%). There were weak correlations between outdoor area (r = -0.28), building design and facilities (r = -0.26), and equipment (r = -0.36) with the concentration of E. coli in the drinking water produced. Conclusion: Some drinking water from DAMIU did not meet the Ministry of Health's standards. Although there was a weak relationship between EHR and E. coli concentration, local health authorities should intervene to improve hygiene and sanitation practices at DAMIU. Additionally, increasing the awareness of depot owners or managers to test their drinking water and improve hygiene practices regularly is essential to ensure water safety.